State of the Contemporary Criminal Law Policy of Russia - ROGOVA, Evgeniya Viktorovna; KARNOVICH, Sergey Anatolievich; EFREMOVA, Marina Aleksandrovna; IVUSHKINA, Olga Viktorovna; LAIKOVA, Elena Aleksandrovna (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
This paper covers on the contemporary state of the criminal law policy of the Russian Federation. The authors state that the criminal law policy is a component of the governmental criminal law policy along with criminal procedures, penal, criminal investigation policies. The analysis of the contemporary state of crime and the current criminal law evidences insufficiently high level of the efficiency of the criminal law policy of the Russian Federation at the present stage. This paper covers on problematic issues arising in connection with continuous restructuring of the criminal law. The authors come to a conclusion that protection of human values in differentiation of criminal liability and finding reasonable balance between strict liability for grave offences and lenient punishment for small and medium gravity crimes should become a priority of the criminal law policy of Russia. The authors conclude on the need for development and approval of scientific criminology-based concept of Russia’s criminal law policy reflecting the state of the contemporary society.